Analysis of Escherichia coli O157:H7 Survival in Ovine or Bovine Manure and Manure Slurry - Kudva, Indira T. (American Society for Microbiology, 1998)
Farm animal manure or manure slurry may disseminate, transmit, or propagate Escherichia coli O157:H7. In this study, the survival and growth of E. coli O157:H7 in ovine or bovine feces under various experimental and environmental conditions were determined. A manure pile collected from experimentally inoculated sheep was incubated outside under fluctuating environmental conditions. E. coli O157:H7 survived in the manure for 21 months, and the concentrations of bacteria recovered ranged from <10(2) to 10(6) CFU/g at different times over the course of the experiment. The DNA fingerprints of E. coli O157:H7 isolated at month 1 and month 12 were identical or very similar. A second E. coli O157:H7-positive ovine manure pile, which was periodically aerated by mixing, remained culture positive for 4 months. An E. coli O157:H7-positive bovine manure pile was culture positive for 47 days. In the laboratory, E. coli O157:H7 was inoculated into feces, untreated slurry, or treated slurry and incubated at −20, 4, 23, 37, 45, and 70°C. E. coli O157:H7 survived best in manure incubated without aeration at temperatures below 23°C, but it usually survived for shorter periods of time than it survived in manure held in the environment. The bacterium survived at least 100 days in bovine manure frozen at −20°C or in ovine manure incubated at 4 or 10°C for 100 days, but under all other conditions the length of time that it survived ranged from 24 h to 40 days. In addition, we found that the Shiga toxin type 1 and 2 genes in E. coli O157:H7 had little or no influence on bacterial survival in manure or manure slurry. The long-term survival of E. coli O157:H7 in manure emphasizes the need for appropriate farm waste management to curtail environmental spread of this bacterium. This study also highlights the difficulties in extrapolating laboratory data to on-farm conditions.